Cover Jurnal Fitopatologi Vol. 17 No. 1, Januari 2021 (Jurnal Fitopatologi Indonesia, 2021)
This editorial contains the front cover, editorial page and back cover of the Indonesian Journal of Phytopathology, Volume 17, No. 1, January 2021.